Conjugated linoleic acid nano-emulsion and preparation method thereof

By using N-succinyl chitosan and Fe2+ ions to coat conjugated linoleic acid, a stable nanoemulsion was formed, which solved the problem of instability of conjugated linoleic acid, significantly improved its stability and bioavailability, and Enhanced antioxidant performance and achieve protective effect on oxidation.

CN119184303APending Publication Date: 2024-12-27FENCHEM BIOTECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411608165.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The chemical properties of conjugated linoleic acid are unstable and are easily affected by light, heat, oxygen and other factors and oxidation and deterioration, resulting in a decrease in biological activity and may produce oxidation products that are harmful to the human body. Existing nanoemulsions are difficult to provide sufficient protection.

Method used

The composite formed by N-succinyl chitosan and Fe2+ ions is coated with conjugated linoleic acid to form a stable nanoemulsion, improve antioxidant performance and stability, and enhance the stability of the emulsifier and antioxidant. Bioavailability.

Benefits of technology

显著提高了共轭亚油酸的稳定性和生物利用度,防止氧化降解,增强了抗氧化性能,形成的纳米乳液在光、热、氧等因素下更加稳定,且制备过程采用天然原料无有毒 The emission of hazardous substances meets the requirements of green and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119184303A_ABST
    Figure CN119184303A_ABST
Patent Text Reader

Abstract

The invention discloses a conjugated linoleic acid nano-emulsion and a preparation method thereof, and belongs to the technical field of nano-emulsion preparation, the conjugated linoleic acid is wrapped in a nanoscale carrier material by using the excellent coating performance of N-succinyl chitosan and the catalytic performance of Fe < 2 + > ions, and the stable nano-emulsion is formed. The nano-emulsion prepared by the invention not only has efficient oxidation resistance, but also can effectively protect the conjugated linoleic acid from being interfered by external environmental factors, and the stability and bioavailability of the conjugated linoleic acid are improved, so that the application range of the conjugated linoleic acid is widened; the formed nano-emulsion form is beneficial to absorption and utilization of conjugated linoleic acid in vivo, and the bioavailability of the conjugated linoleic acid is improved; and natural raw materials are adopted in the whole preparation process, toxic and harmful substances are not discharged, and the green and environment-friendly requirements are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanoemulsion preparation, and specifically relates to a conjugated linoleic acid nanoemulsion and a preparation method thereof. Background Art

[0002] With the growing demand for healthy food and functional additives, conjugated linoleic acid (CLA) has attracted much attention due to its unique biological activity and health benefits. CLA is a naturally occurring polyunsaturated fatty acid that is mainly found in meat and dairy products of ruminants (such as cattle and sheep). It has multiple physiological functions such as antioxidant, anti-inflammatory, anti-cancer, fat metabolism promotion, and blood lipid regulation. However, despite these significant advantages, CLA's chemical properties are relatively unstable and it is easily affected by factors such as light, heat, and oxygen, which can cause oxidation and deterioration. This not only reduces its biological activity, but may also produce oxidation products that are harmful to the human body.

[0003] In order to overcome the poor stability of CLA, various protection strategies are constantly being explored. Among them, nanoemulsion, as an effective delivery system, can significantly improve the stability, solubility and bioavailability of active ingredients by reducing particle size, increasing surface area and improving solubility. However, simple nanoemulsions often cannot provide sufficient protection to prevent oxidative degradation of CLA.

[0004] As a chitosan derivative, N-succinyl chitosan not only retains the original excellent biocompatibility and film-forming properties of chitosan by introducing succinyl groups, but also enhances its water solubility and antioxidant properties. However, this antioxidant property is relatively weak. Summary of the invention

[0005] Purpose of the invention: In order to overcome the shortcomings of the prior art, the present invention provides a conjugated linoleic acid nanoemulsion and a preparation method thereof, utilizing the excellent coating performance of N-succinyl chitosan and Fe 2+ The catalytic properties of ions are used to encapsulate CLA in nanoscale carrier materials to form a stable nanoemulsion. The prepared nanoemulsion not only has significant antioxidant properties, but also has improved stability and bioavailability.

[0006] Technical solution: To achieve the above purpose, the present invention adopts the following technical solution:

[0007] A conjugated linoleic acid nanoemulsion, wherein the outermost layer of the nanoemulsion is a continuous water phase, and the water phase contains N-succinyl chitosan and Fe 2+ The conjugated linoleic acid oil droplets coated with the complex formed by ions include the following components by weight percentage:

[0008] N-succinyl chitosan: 1%-10%, as wall material and stabilizer;

[0009] FeSO4·(H2O)7: 0.1% to 1%, as a stabilizer for the wall material of N-succinyl chitosan and an enhancer of its antioxidant properties;

[0010] Conjugated linoleic acid (CLA): 1% to 8%, as a core antioxidant ingredient;

[0011] Edible oil: 10% to 30%, as oil phase;

[0012] Emulsifier: 0.5% to 3%, used to assist the emulsification process, selected from polyglycerol fatty acid esters, sucrose fatty acid esters, etc.;

[0013] Water: the balance, as the water phase;

[0014] The preparation method of N-succinyl chitosan is as follows: 2 g of chitosan is added to 40 mL of DMSO, stirred evenly, and then 4.0 g of succinic anhydride is slowly added, reacted at 65° C. for 6 h, the filtrate is filtered out, and the precipitate is dissolved in ethanol at room temperature for 1 h, 1 mol·L -1 The pH of the solution was adjusted to 10.0-12.0 with NaOH and filtered. The precipitate was dissolved in 90 mL of distilled water and 270 mL of acetone was added. The precipitate was washed with ethanol and acetone respectively. The obtained product was dried in an oven at 50°C.

[0015] The nanoemulsion may also include an antioxidant selected from vitamin E, the weight percentage of which is 0.01% to 0.1% of the total weight of the nanoemulsion, for further enhancing the antioxidant properties of the emulsion.

[0016] The preparation method of the above conjugated linoleic acid nanoemulsion comprises the following steps:

[0017] (1) N-succinyl chitosan-Fe 2+ Preparation of the complex: weigh 3-10 g N-succinyl chitosan into 30-50 g sodium citrate buffer (pH 4.6), add 1-10 mg FeSO4·(H2O)7, stir at room temperature for 3-6 h, and set aside;

[0018] (2) Preparation of conjugated linoleic acid oil phase: dissolve 0.5-5 g of conjugated linoleic acid in 10-30 g of edible oil, heat at 40-60° C. and stir until completely dissolved to form an oil phase;

[0019] (3) Preparation of aqueous phase: 0.5 g to 3 g of polyglycerol fatty acid ester, sucrose fatty acid ester (mass ratio is 1:1) and the rest of water are mixed and heated to a temperature close to that of the oil phase;

[0020] (4) Preparation of primary emulsion: slowly add the oil phase into the water phase while stirring to form a primary emulsion;

[0021] (5) Preparation of nanoemulsion: adjusting the pH to between 4 and 5 with citric acid, stirring the primary oil-in-water emulsion with a homogenizer at a rate of 4000 to 7000 r / min for a homogenization time of 2 to 10 minutes to obtain a conjugated linoleic acid nanoemulsion;

[0022] (6) N-succinyl chitosan-Fe 2+ The complex was added to conjugated linoleic acid nanoemulsion, N-succinyl chitosan-Fe 2+ The complex spontaneously adsorbed onto the surface of the conjugated linoleic acid oil droplets to form a dense coating layer, obtaining N-succinyl chitosan-Fe 2+ Encapsulated conjugated linoleic acid nanoemulsion.

[0023] In the above steps, an antioxidant may be added after the pH is adjusted with citric acid in step (5) to further enhance the antioxidant properties of the emulsion.

[0024] Beneficial effects: The present invention provides a conjugated linoleic acid nanoemulsion and a preparation method thereof. Compared with the prior art, the beneficial effects are as follows:

[0025] 1) The nanoemulsion prepared by the present invention is composed of a continuous aqueous phase, N-succinyl chitosan and Fe 2+ The conjugated linoleic acid oil droplets are coated with the complex formed by ions, and the water phase is surrounded by the outside of the coating layer, providing a stable liquid environment for the entire system; at the same time, there are hydrogen bonds and other interactions between the solvent molecules (such as water molecules) in the water phase and the N-succinyl chitosan molecules in the coating layer, which further enhances the stability of the system; the coating layer N-succinyl chitosan-Fe 2+ The complex can be tightly wrapped on the surface of the conjugated linoleic acid oil droplets to form a continuous and dense coating layer, which can significantly improve the stability of the nanoemulsion and prevent the aggregation and sedimentation between the oil droplets;

[0026] 2) Coating layer N-succinyl chitosan-Fe 2+ N-succinyl chitosan and Fe in the complex 2+ Combination, Fe 2+ The introduction of further enhances the stability of the wall material, has a synergistic effect, enhances the antioxidant properties of the complex, and forms a stable metal-polysaccharide complex. This complex, as a coating material, can not only effectively prevent the oxidative degradation of conjugated linoleic acid, but also improve its dispersibility and stability in water; it can effectively protect conjugated linoleic acid from damage by light, heat, oxygen and other factors;

[0027] 3) The nanoemulsion formed is conducive to the absorption and utilization of conjugated linoleic acid in the body, thereby improving its bioavailability; and the entire preparation process uses natural raw materials, has no toxic or harmful substances emitted, and meets green environmental protection requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Attached Figure 1 This is a state diagram of the initial emulsion in an embodiment of the present invention;

[0029] Attached Figure 2 This is a state diagram of the emulsion on the 7th day of the centrifugal stability test in an embodiment of the present invention;

[0030] Attached Figure 3 This is a state diagram of the emulsion on the 14th day of the centrifugal stability test in an embodiment of the present invention;

[0031] Attached Figure 4 This is a state diagram of the emulsion on the 28th day of the centrifugal stability test in an embodiment of the present invention;

[0032] Attached Figure 5 This is a diagram of the state of the emulsion after the freeze-thaw cycle test in an embodiment of the present invention;

[0033] Attached Figure 6 This is a diagram showing the state of the emulsion after the oxidation stability test in an embodiment of the present invention. DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with the accompanying drawings.

[0035] Example 1

[0036] Highly effective antioxidant N-succinyl chitosan-Fe 2+ The preparation method of the coated conjugated linoleic acid nanoemulsion comprises the following steps:

[0037] (1) N-succinyl chitosan-Fe 2+ Preparation of the composite: weigh 6 g of N-succinyl chitosan into 40 g of sodium citrate buffer (pH 4.6), add 6 mg of FeSO4·(H2O)7, stir at room temperature for 3.5 h, and set aside;

[0038] (2) Preparation of conjugated linoleic acid oil phase: 4 g of conjugated linoleic acid was dissolved in 25 g of edible oil, heated at 50° C. and stirred until completely dissolved to form an oil phase;

[0039] (3) Preparation of aqueous phase: Mix 2.5 g of polyglycerol fatty acid ester, sucrose fatty acid ester and the remainder of water, and heat to a temperature close to that of the oil phase;

[0040] (4) Preparation of primary emulsion: slowly add the oil phase into the water phase while stirring to form a primary emulsion;

[0041] (5) Preparation of nanoemulsion: The pH was adjusted to 4.6 with citric acid, 0.05% vitamin E was added, and the primary oil-in-water emulsion was stirred with a homogenizer at 6000 r / min for 4 minutes to obtain a conjugated linoleic acid nanoemulsion;

[0042] (6) N-succinyl chitosan-Fe 2+ The complex was added to conjugated linoleic acid nanoemulsion, N-succinyl chitosan-Fe 2+ The complex spontaneously adsorbed onto the surface of the conjugated linoleic acid oil droplets to form a dense coating layer, obtaining N-succinyl chitosan-Fe 2+ Encapsulated conjugated linoleic acid nanoemulsion.

[0043] Comparative Example 1

[0044] (1) Preparation of conjugated linoleic acid oil phase: 4 g of conjugated linoleic acid was dissolved in 25 g of edible oil, heated at 50° C. and stirred until completely dissolved to form an oil phase;

[0045] (2) Preparation of aqueous phase: Mix 2.5 g of polyglycerol fatty acid ester, sucrose fatty acid ester and the remainder of water, and heat to a temperature close to that of the oil phase;

[0046] (4) Preparation of primary emulsion: slowly add the oil phase into the water phase while stirring to form a primary emulsion;

[0047] (5) Preparation of nanoemulsion: The pH was adjusted to 4.6 with citric acid, 0.05% vitamin E was added, and the primary oil-in-water emulsion was stirred with a homogenizer at 6000 r / min for 4 minutes to obtain conjugated linoleic acid nanoemulsion.

[0048] Example 2

[0049] Highly effective antioxidant N-succinyl chitosan-Fe 2+ The preparation method of the coated conjugated linoleic acid nanoemulsion comprises the following steps:

[0050] (1) N-succinyl chitosan-Fe 2+ Preparation of the composite: weigh 3 g of N-succinyl chitosan into 35 g of sodium citrate buffer (pH 4.6), add 5 mg of FeSO4·(H2O)7, stir at room temperature for 4 h, and set aside;

[0051] (2) Preparation of conjugated linoleic acid oil phase: 2 g of conjugated linoleic acid was dissolved in 20 g of edible oil, heated at 45° C. and stirred until completely dissolved to form an oil phase;

[0052] (3) Preparation of aqueous phase: Mix 2 g of polyglycerol fatty acid ester, sucrose fatty acid ester and the remainder of water, and heat to a temperature close to that of the oil phase;

[0053] (4) Preparation of primary emulsion: slowly add the oil phase into the water phase while stirring to form a primary emulsion;

[0054] (5) Preparation of nanoemulsion: The pH was adjusted to 4.5 with citric acid, 0.06% vitamin E was added, and the primary oil-in-water emulsion was stirred with a homogenizer at 5000 r / min for 6 minutes to obtain a conjugated linoleic acid nanoemulsion;

[0055] (6) N-succinyl chitosan-Fe 2+ The complex was added to conjugated linoleic acid nanoemulsion, N-succinyl chitosan--Fe 2+ The complex spontaneously adsorbed onto the surface of the conjugated linoleic acid oil droplets to form a dense coating layer, obtaining N-succinyl chitosan-Fe 2+ Encapsulated conjugated linoleic acid nanoemulsion.

[0056] Comparative Example 2

[0057] (1) Preparation of N-succinyl chitosan solution: weigh 3 g of N-succinyl chitosan into 35 g of sodium citrate buffer (pH 4.6), add 5 mg of FeSO4·(H2O)7, stir at room temperature for 4 h, and set aside;

[0058] (2) Preparation of conjugated linoleic acid oil phase: 2 g of conjugated linoleic acid was dissolved in 20 g of edible oil, heated at 45° C. and stirred until completely dissolved to form an oil phase;

[0059] (3) Preparation of aqueous phase: Mix 2 g of polyglycerol fatty acid ester, sucrose fatty acid ester and the remainder of water, and heat to a temperature close to that of the oil phase;

[0060] (4) Preparation of primary emulsion: slowly add the oil phase into the water phase while stirring to form a primary emulsion;

[0061] (5) Preparation of nanoemulsion: The pH was adjusted to 4.5 with citric acid, 0.06% vitamin E was added, and the primary oil-in-water emulsion was stirred with a homogenizer at 5000 r / min for 6 minutes to obtain conjugated linoleic acid nanoemulsion.

[0062] Example 3

[0063] Highly effective antioxidant N-succinyl chitosan-Fe 2+ The preparation method of the coated conjugated linoleic acid nanoemulsion comprises the following steps:

[0064] (1) N-succinyl chitosan-Fe 2+Preparation of the composite: weigh 6.5 g N-succinyl chitosan into 40 g sodium citrate buffer (pH 4.6), add 7 mg FeSO4·(H2O)7, stir at room temperature for 4.5 h, and set aside;

[0065] (2) Preparation of conjugated linoleic acid oil phase: 4.5 g of conjugated linoleic acid was dissolved in 30 g of edible oil, heated at 50° C. and stirred until completely dissolved to form an oil phase;

[0066] (3) Preparation of aqueous phase: Mix 3 g of polyglycerol fatty acid ester, sucrose fatty acid ester and the remainder of water, and heat to a temperature close to that of the oil phase;

[0067] (4) Preparation of primary emulsion: slowly add the oil phase into the water phase while stirring to form a primary emulsion;

[0068] (5) Preparation of nanoemulsion: adjust the pH to 4.8 with citric acid. Add 0.05% vitamin E, stir the primary oil-in-water emulsion with a homogenizer at 7000 r / min for 3.5 minutes to obtain conjugated linoleic acid nanoemulsion;

[0069] (6) N-succinyl chitosan-Fe 2+ The complex was added to conjugated linoleic acid nanoemulsion, N-succinyl chitosan-Fe 2+ The complex spontaneously adsorbed onto the surface of the conjugated linoleic acid oil droplets to form a dense coating layer, obtaining N-succinyl chitosan-Fe 3+ Encapsulated conjugated linoleic acid nanoemulsion.

[0070] Comparative Example 3

[0071] (1) N-succinyl chitosan-Fe 2+ Preparation of the composite: weigh 6.5 g N-succinyl chitosan into 40 g sodium citrate buffer (pH 4.6), add 7 mg FeSO4·(H2O)7, stir at room temperature for 4.5 h, and set aside;

[0072] (2) Preparation of conjugated linoleic acid oil phase: 4.5 g of conjugated linoleic acid was dissolved in 30 g of edible oil, heated at 50° C. and stirred until completely dissolved to form an oil phase;

[0073] (3) Preparation of aqueous phase: Mix 3 g of polyglycerol fatty acid ester, sucrose fatty acid ester and the remainder of water, and heat to a temperature close to that of the oil phase;

[0074] (4) Preparation of primary emulsion: slowly add the oil phase into the water phase while stirring to form a primary emulsion;

[0075] (5) Preparation of nanoemulsion: The pH was adjusted to 7 with citric acid. 0.05% vitamin E was added, and the primary oil-in-water emulsion was stirred with a homogenizer at 7000 r / min for 3.5 minutes to obtain conjugated linoleic acid nanoemulsion.

[0076] Characterization experiments

[0077] Particle size and zeta potential determination

[0078] The average particle size and Zeta potential of the nanoemulsions in the above examples and comparative examples were measured at room temperature using a nanoparticle size potentiometer, with the equilibrium time set to 60 s, the scanning interval to 10 s, the temperature to 25° C., and each sample was analyzed three times in parallel. The results are shown in Table 1:

[0079] Table 1 Particle size-Zeta potential table

[0080]

[0081] The particle size results showed that the use of N-succinyl chitosan-Fe 2+ The particle size of the nanoemulsion prepared by the composite is significantly smaller. 2+ The particle size of the nanoemulsion prepared by the composite is significantly larger than that of the nanoemulsion without Fe immobilization. 2+ The smaller the particle size, the slower the buoyancy and the greater the electrostatic repulsion. By strengthening the repulsion between droplets, the emulsion can be prevented from agglomerating. Zeta potential is a measure of the strength of mutual repulsion or attraction between particles. It is an important indicator for judging the stability of particles in nanoemulsions. The smaller the molecule or dispersed particle, the higher the absolute value of Zeta potential (positive or negative), and the more stable the system. The results show that N-succinyl chitosan-Fe 2+ The nanoemulsion prepared by the composite is significantly higher than that without immobilized Fe 2+ The results of comparative example 3 show that the particle size of the nanoemulsion system under acidic conditions is smaller and the Zeta potential is higher.

[0082] Thermodynamic stability test

[0083] Good thermodynamic stability gives the nanoemulsion a longer shelf life. In order to determine the thermodynamic stability, centrifugal stability tests and freeze-thaw cycle tests were performed:

[0084] Centrifugal stability test: Take 10 ml of the emulsion and centrifuge at 4000 rpm for 15 min to observe whether there is phase separation, precipitation, emulsification, lysis or turbidity. Perform the test every 7 days (7th day, 14th day, 21st day, 28th day) until 28 days of storage;

[0085] Freeze-thaw cycle test: After being frozen at -20℃ for 24 hours, the samples were taken out and stored at room temperature. The separation, precipitation, emulsification and cracking parameters were observed.

[0086] like Figure 1-4 As shown, even after 28 days, no phase separation or emulsion cracking was observed in the centrifugation experiment for the nanoemulsions obtained in Examples 1-3. Phase separation and emulsion cracking were observed in the centrifugation experiment for the nanoemulsions obtained in Comparative Example 1 on the 7th day, and phase separation and emulsion cracking were observed in the centrifugation experiment for the nanoemulsions obtained in Comparative Examples 2 and 3 on the 14th day.

[0087] like Figure 5 As shown, the nanoemulsions obtained in Examples 1-3 did not undergo phase separation or emulsion cracking in the freeze-thaw experiments; the nanoemulsions obtained in Comparative Examples 1-3 all showed phase separation in the freeze-thaw experiments, and the emulsion cracking in Comparative Example 1 was the most serious, indicating that N-succinyl chitosan-Fe 2+ The thermodynamic stability of the nanoemulsion with the composite as the wall material is very good. 2+ The whole nanoemulsion structure system is strengthened, making the whole system more stable. A comprehensive comparison of Examples 1-3 and Comparative Example 3 shows that the control of acidic conditions is more effective for the stability of the whole nanoemulsion system.

[0088] Oxidative stability determination

[0089] The nanoemulsion was measured by OXITEST oxidation stability analyzer to obtain the oxidation curve of the sample. The induction period (IP) is the time required to reach the starting point of oxidation, corresponding to the detectable degree of rancidity or sudden change in oxidation rate. The longer the induction period, the higher the antioxidant activity of the sample. Test conditions: 90°C, oxygen: 6 bar.

[0090] like Figure 6 As shown, the experimental results show that N-succinyl chitosan-Fe 2+ The nanoemulsion induction period of the composite as wall material is significantly higher, and Fe 2+ The addition of enhances the antioxidant properties of the nanoemulsion and has higher antioxidant activity.

[0091] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A conjugated linoleic acid nanoemulsion, characterized in that: The nanoemulsion is composed of a continuous aqueous phase, N-succinyl chitosan and Fe 2+ ion-formed complexes coated with conjugated linoleic acid oil droplets.

2. The conjugated linoleic acid nanoemulsion according to claim 1, characterized in that The nanoemulsion comprises the following components by weight percentage: 1%-10% N-succinyl chitosan, 0.1% to 1% FeSO4·(H2O)7, 1% to 8% conjugated linoleic acid, 10% to 30% edible oil, 0.5% to 3% emulsifier, and the balance is water.

3. The conjugated linoleic acid nanoemulsion according to claim 1 or 2, characterized in that: The nanoemulsion comprises an antioxidant, and the weight percentage of the antioxidant is 0.01% to 0.1% of the total weight of the nanoemulsion.

4. The method for preparing the conjugated linoleic acid nanoemulsion according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) N-succinyl chitosan-Fe 2+ Preparation of the complex: Add N-succinyl chitosan to an acidic buffer, add FeSO4·(H2O)7, and stir at room temperature for 3-6 hours for use; (2) Preparation of conjugated linoleic acid oil phase: dissolving conjugated linoleic acid in edible oil, heating at 40-60° C. and stirring until completely dissolved to form an oil phase; (3) Preparation of water phase: Mix the emulsifier with water and heat to a temperature close to that of the oil phase; (4) Preparation of primary emulsion: slowly add the oil phase into the water phase while stirring to form a primary emulsion; (5) Preparation of nanoemulsion: adjusting the pH to acidic, homogenizing the primary emulsion to obtain conjugated linoleic acid nanoemulsion; (6) N-succinyl chitosan-Fe 2+ The complex was added to conjugated linoleic acid nanoemulsion, N-succinyl chitosan-Fe 2+ The complex spontaneously adsorbed onto the surface of the conjugated linoleic acid oil droplets to form a dense coating layer, obtaining N-succinyl chitosan-Fe 2+ Encapsulated conjugated linoleic acid nanoemulsion.

5. The method for preparing the conjugated linoleic acid nanoemulsion according to claim 4, characterized in that: The acidic buffer solution is a sodium citrate buffer solution with a pH of 4.

6.

6. The method for preparing the conjugated linoleic acid nanoemulsion according to claim 4 or 5, characterized in that: The preparation method of N-succinyl chitosan is as follows: 2 g of chitosan is added to 40 mL of DMSO, stirred evenly, and then 4.0 g of succinic anhydride is slowly added, reacted at 65° C. for 6 h, the filtrate is filtered out, and the precipitate is dissolved in ethanol at room temperature for 1 h, 1 mol·L - 1 The pH of the solution was adjusted to 10.0-12.0 with NaOH and filtered. The precipitate was dissolved in 90 mL of distilled water and 270 mL of acetone was added. The precipitate was washed with ethanol and acetone respectively. The obtained product was dried in an oven at 50°C.

7. The method for preparing the conjugated linoleic acid nanoemulsion according to claim 4, characterized in that: The emulsifier is polyglycerol fatty acid ester and sucrose fatty acid ester in a mass ratio of 1:

1.

8. The method for preparing the conjugated linoleic acid nanoemulsion according to claim 4, characterized in that: In step (5), the pH is adjusted to 4-5.

9. The method for preparing the conjugated linoleic acid nanoemulsion according to claim 4 or 8, characterized in that: In step (5), an antioxidant is added after adjusting the pH.

10. The method for preparing the conjugated linoleic acid nanoemulsion according to claim 4, characterized in that: The homogenization conditions are: rotation speed of 4000-7000r / min and time of 2-10 minutes.